EVIDENCE FOR ANOXIA IN DEEP ENVIRONMENTS OF NORTHEAST ASIA AT THE PERMIAN-TRIASSIC TRANSITION - Biakov A.S.; Vedernikov I.L. (My University, 2007)
It is well known that the Permian–Triassic transition was marked by significant changes in the biota and sedimentation settings. Evidence for the development of anoxic environments in various world areas during events at the Permian–Triassic transition in both shallow- and deep-water settings. Such data have been unavailable thus far for the Russian territory. The study of Permian–Triassic boundary deepwater sediments in Northeast Asia provided the first evidence for H2S contamination of bottom waters in this region. Both shallow- and deep-sea basins existed in Northeast Asia during the Permian Period: Ayan-Yuryakh, Balygychan, Sugoi, and Gizhiga. They were characterized by avalanche sedimentation, which was responsible for accumulation of thick (up to 7 km) sandy–clayey and volcanogenic (frequently, turbidite) sediments with impoverished fossil assemblages. The fossils are represented by Inoceramus-like bivalves and subordinate ctenodont bivalves and gastropods (Straparolus).
Keywords: Triassic; Permian; Mesozoic::Triassic; Мезозой::Триасовая; Paleozoic::Permian; Палеозой::Пермская